Layanan Konseling Kelompok dengan Metode Muhadhoroh untuk Mengatasi Kepercayaan Diri Remaja - Usman, Al; Razzaq, Abdur; Marianti, Lena (Journal of Society Counseling, 2025)
This research is entitled "Group Counseling Services Using the Muhadhoroh Method to Overcome Self-Confidence of Adolescents at Nurul Huda Mosque RT 05 RW 09" This research aims to help overcome the problem of self-confidence among adolescents at Nurul Huda Mosque in RT 05 RW 09, as well as to find out how group counseling services work. Muhadhoroh method in overcoming the self-confidence of teenagers at the Nurul Huda Mosque. This type of research is descriptive research with a qualitative approach, data collection tools are interviews, observation, and documentation. Meanwhile, technical data analysis includes data reduction, data display, conclusions, and verification. The subjects in this research were seven mosque teenagers. The results of this research show that mosque teenagers lack self-confidence, such as doubting their ability to face situations or challenges and lacking a sense of responsibility, which can cause them to continue to be in a high state of worry, feel inadequate in making decisions or steps to achieve a goal. The stages of group counseling using the muhadhoroh method to overcome the self-confidence of mosque teenagers have group counseling stages, namely the initial stage, transition stage, activity stage, and final stage, and the application of muhadhoroh is the behavioral practice that is applied, building client motivation, giving feedback, speaking as the first person, praising the client's courage and giving confidence in the activities that have just been carried out in the group counseling process to be applied in the next life.